‘Good’ and ‘bad’ stem cell research: How India's scientists view providers of unproven stem cell treatments - Rohini Kandhari (SSM: Qualitative Research in Health, 2023)
In this article, I explore the opinions of India's stem cell scientists on unproven and unregulated stem cell treatment provision in the country's private health sector. Drawing on interviews, I describe three themes, namely ethical responsibility; exaggerated timelines for stem cell cures; and the scientific method to demonstrate how scientists make distinctions between themselves as producers of ‘good stem cell research’ and treatment providers who practice ‘bad stem cell research’. Excerpts from my interviews with treatment providers interrupt the discussions in the themes, offering insights on conflicting views of medical professionals. I analyse the themes using the conceptual framework of ‘boundary-work’ that Gieryn developed in order to examine how scientists respond to challenges to their intellectual authority in particular scientific fields. A policy environment that promotes product development posed a threat to the integrity of basic science according to stem cell scientists who simultaneously reflected on solutions to advancing India's stem cell field by promoting the role of clinician-researchers as mediators between medicine and science. According to Gieryn, depending on what is at stake such as funding and public support, scientists redraw boundaries in order to secure their position in relation to competing groups. In this instance, I argue that the expectations of translational research, demanded that scientists examine the boundaries drawn between themselves and clinicians with the purpose of also including the latter in stem cell science rather than for excluding contenders, as Gieryn's notion of boundary-work suggested.